Studi Literatur Mengenai Prediksi Kepuasan GrabFood Menggunakan Machine Learning - Martiani, Evi; Setyanto, Arief; Nasiri, Asro (DIELEKTRIKA, 2024)
The rapid growth of food delivery applications, such as GrabFood, has revolutionized the way consumers access and enjoy their favorite meals. Ensuring customer satisfaction is crucial for these platforms to maintain their competitive edge and foster customer loyalty. If many customers are not satisfied with the service or anything provided by GrabFood, it is possible that they will leave the application soon or later. This research is aimed to review some literature related to customer satisfaction of the food delivery application with the use of machine learning. From this review, one can have more information and insight on how machine learning can help to find the satisfaction level of the customers. The method which is used in this research is literature review which reviews the collection of literature. Varied literature with different variables has been resulted from this research. Many of them use different methods of machine learning.